PEGEMBANGAN PERANGKAT PEMBELAJARAN TERPADU TIPE NETWORKED DENGAN SCIENCES, TECHNOLOGY AND SOCIETY APPROACH UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SEKOLAH DASAR - Evita Gustarina (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2018)
ABSTRACTThis research aims to produce a decent learning instrument used for integrated learning with science, technology and society approach. Eligibility can be seen from the definition, planning, validity, practicality, effectiveness, learning outcomes of the learning that has been developed. This type of research is research development. Learning instrument are developed namely RPP, LKS, BAS, ang EHB. Learning instrument using one group pretest posttest design experimental in the five grade SD IT Generasi Rabbani and SD IT Al Aufa. Methods of data collection include validity, observation and tests. Data analysis using the percentage and the analysis of N-Gain and the analysis of anova. The results showed that 1) Validity instrument developed the content validity as seen from the study implementation plan, is student activity sheets, student's Textbook and student assessment each have average 3.54; 3.21; 3.27 and 3.15 category either, as well as the readability of the student's Textbook  and is Student Activity Sheets as developed can be categorized either. 2) The practicability of learning seen from instrument to be completed 100% done with the results assessment of to be completed class A at 3.71; class B 3.76; class C 3.71 excellent category. 3) Effectiveness in terms of student response devices shows the percentage of response very well to learning activities, students in grade class A 86,85%, class B 85.68%  and class C 88.08% of the activity that the activity shows the percentage of rated very good in learning, and analysis the magnitude of the increase in the results of a study using N-Gain shows the Gain of the average high on all three categories class as well as an analysis with anova test showed no There is a difference of the average results of student learning in the classroom while pretest or posttest. Based on these results it can be concluded that the resulting instrument is eligible to apply to learning because it has met the three criteria, namely validity, practicality, effectiveness, results and learning activities are increasing. Keywords: Development, integrated learning type of Networked, Sciences, Technology and Society Approach, learning activities, the results of the study. ABSTRAK                                                                                          Penelitian ini bertujuan untuk menghasilkan perangkat pembelajaran terpadu tipe networked dengan science, technology and society approach di kelas V Sekolah Dasar yang memenuhi syarat kevalidan, kepraktisan dan keefektifan sehingga dapat meningkatkan hasil belajar siswa. Jenis penelitian adalah penelitian pengembangan. Pengembangan perangkat pembelajaran terdiri atas RPP, LKS, BAS dan EHB. Perangkat pembelajaran menggunakan desain eksperimen one group pretest posttest design. Pada siswa kelas V di SD IT Generasi Rabbani dan SD IT Al Aufa. Metode Pengumpulan data meliputi validitas, observasi dan tes. Analisis data menggunakan persentase, analisis N-Gain dan analisis uji anova.  Hasil penelitian menunjukkan bahwa 1) Kevalidan perangkat yang dikembangkan dilihat dari validitas isi RPP, LKS, BAS, dan EHB masing-masing memiliki rata-rata 3,54; 3,21; 3,27 dan 3,15 berkategori baik, serta Keterbacaan BAS dan LKS yang dikembangkan dapat dikategorikan baik. 2) Kepraktisan perangkat pembelajaran dilihat dari keterlaksanaan 100% terlaksana dengan hasil penilaian keterlaksanaan RPP di kelas A 3,71;  Kelas B 3,76;  Kelas C 3,71 berkategori sangat baik  3) Keefektifan perangkat ditinjau dari respon siswa menunjukkan persentase respon sangat baik terhadap pembelajaran,  aktivitas siswa di kelas A 86,85%, kelas B 85,68% dan kelas C 88,08% dari aktivitas yang dinilai menunjukkan persentase aktivitas sangat baik dalam pembelajaran, dan Analisis besarnya peningkatan hasil belajar dengan menggunakan  N-Gain menunjukkan peningkatan rata-rata berkategori tinggi pada ketiga kelas implementasi serta Analisis dengan uji anova menunjukkan tidak terdapat perbedaan rata-rata hasil belajar siswa di kelas implementasi baik saat pretest maupun posttest. Berdasarkan hasil tersebut maka dapat disimpulkan bahwa perangkat yang dihasilkan layak untuk diterapkan pada pembelajaran karena telah memenuhi tiga kriteria yaitu kevalidan, kepraktisan, keefektifan sehingga dapat meningkatkan hasil belajar siswa.           Kata Kunci:  Pengembangan Perangkat, Pembelajaran terpadu tipe Networked, Sciences, Technology and  Society Approach, Hasil Belajar.